Thermally stable electrostrains and composition-dependent electrostrictive coefficient Q33 in lead-free ferroelectric ceramics. Issue 17 (1st December 2019) - Jin, Li; Pang, Jing; Pu, Yongping; Xu, Ning; Tian, Ye; Jing, Ruiyi; Du, Hongliang; Wei, Xiaoyong; Xu, Zhuo; Guo, Dong; Xu, Jie; Gao, Feng
Abstract: The electrostrictive effect plays an important role in the electric-field-induced strain (electrostrain) of ferroelectric ceramics. This is especially true in high-electric-field regions because of the high-order coupling effect between electric-field-induced polarization and electrostrain. In this study, the electrostrictive properties of (1- x )(Bi0.5 Na0.5 )TiO3 - x (Ba0.85 Ca0.15 )(Ti0.9 Zr0.1 )O3 (BNT- x BCZT, x = 0.1, 0.2, 0.3, 0.4, 0.5, and 0.6) ferroelectric ceramics were investigated in the temperature range 30 °C–120 °C for obtaining high thermally stable electrostrains and for understanding the effect of composition on the longitudinal electrostrictive coefficient Q 33 . High electrostrains (>0.2% at 60 kV/cm) with good thermal stability (variation of less than 10%) in the tested temperature range were obtained for x = 0.1. Most importantly, Q 33 of BNT- x BCZT ceramics increased almost linearly from 0.0244 m 4 /C 2 to 0.0374 m 4 /C 2 when x increased from 0.1 to 0.6, suggesting a composition-dependent nature. In addition, Q 33 of pure BNT (0.0215 m 4 /C 2 ), which has been unavailable to date, was extracted from this linear relationship. Furthermore, we revealed that the increase in Q 33 is mainly due to the increase in the cell volume. Our results not only clarify the composition effect on Q 33 in BNT- x BCZT ceramics but also provide a way to enhance Q 33 by increasing the cell volume through appropriate doping of ions or perovskite ferroelectric compounds.